2021
DOI: 10.1007/s12231-021-09523-6
|View full text |Cite
|
Sign up to set email alerts
|

Socio–Cultural Significance of Yerba Maté among Syrian Residents and Diaspora

Abstract: Socio-Cultural Significance of Yerba Maté among Syrian Residents and Diaspora. Syria is the world's second-largest importer of the dried leaves of Ilex paraguariensis A.St.-Hil., commonly known as yerba maté. The unique story of yerba maté in the Syrian beverage culture started at the beginning of the twentieth century when Syrian migrants returning from South America brought the beverage with them. The overall aim of our study is to understand yerba maté use among Syrians and its role as an essential part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…We found no recent research on yerba mate consumption patterns among Syrian university students, although Syria is the world's second-largest importer of dried leaves of Ilex paraguariensis A. St.-Hil (Aquifoliaceae) (Sulaiman et al, 2021). The average consumption of mate in our study was consistent with previous research which found that the daily consumption can vary between 1 and 6 Liters per person (Bastos et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…We found no recent research on yerba mate consumption patterns among Syrian university students, although Syria is the world's second-largest importer of dried leaves of Ilex paraguariensis A. St.-Hil (Aquifoliaceae) (Sulaiman et al, 2021). The average consumption of mate in our study was consistent with previous research which found that the daily consumption can vary between 1 and 6 Liters per person (Bastos et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…In Syria, as a part of the Mediterranean basin, cooked vegetables and salads made from wild greens have been particularly important as local traditional foods since ancient times [ 17 ]. However, wild food plants (WFPs) have not been widely studied in the Syrian context [ 18 , 19 ], and while teas prepared from wild plants have been marginally covered [ 20 , 21 , 22 ], there are no studies about the use of wild plants with a focus on the effects of the conflict. On the other hand, studies from surrounding countries, such as Lebanon [ 23 , 24 ], Cyprus [ 25 ], Iraqi-Kurdistan [ 26 ], Palestine [ 27 ], and Turkey [ 28 ] clearly show the importance of wild plants in the food culture of the East Mediterranean region.…”
Section: Introductionmentioning
confidence: 99%
“…Rheum ribes (24) Mentha longifolia (23) Allium paradoxum (21) Tragopogon collinus (16) Eremurus spectabilis (17) Prangos aricakensis (14) The results showed that Kurds in Iran have a slightly higher diversity in ethnobotanical knowledge compared to the Hawramani Kurds in Iraq when considering the results of both groups together [23]. However, by comparing each group separately, we find a roughly similar ethnobotanical diversity.…”
Section: Hawramani Mukriyanimentioning
confidence: 72%
“…The social fabric of the Middle East, especially in the Fertile Crescent region, is highly diverse, with many linguistic, religious, and cultural groups, where Kurds represent an essential part of this mosaic [21]. Mesopotamia, and the regions around it, is a unique hotspot for biocultural diversity and for investigating patterns of traditional wild food plant foraging, considering that this area was home to the first Neolithic communities and has been, over millennia, a crossroad of different civilizations and cultures [16].…”
Section: Introductionmentioning
confidence: 99%